Screening for and uptake of arsenic by hyperaccumulator ferns grown on organic soil - Abu Bakar, Nur Aini (2017)
A brake fern, Pteris vittata L. has been demonstrated to absorb heavy metals, especially arsenic (As) in soil. However, there was a limited study to investigate an interaction between phosphate and arsenic (As) in soil. Therefore, the objective of the study was to investigate suitable fern and condition for accumulation of As from As-rich soil. In the screening study, eight species of ferns, Diplazium velutinum H., Diplazium esculentum (Retz). Sw, Pityrogramma calomenalos (L.) Link, Nephrolepis biserrata (Sw). Schott, Pteris vittata L., Christella arida (D. Don) Holttum, Didymochlaena truncatula (Sw.) J. Sm. and Angiopteris evecta (G. Forst.) Hoffm in Peninsular Malaysia were evaluated on their potential in hyper accumulating As in soil. Uncontaminated soil was collected from Kampung Ulu Chuchoh was spiked with 200 mg AS kg-1 soil using sodium arsenate salt. Three ferns species were grouped as higher As accumulator - P.calomenalos (1552.67 mg kg-1), D.velutinum (975.47 mg kg-1) and P.vittata (947.07 mg kg-1). Since, P. vittata is easily available in large numbers in nursery as compared to two other species, it was selected further in next experiment. In soil incubation study, naturally As-rich soil in Kampung Renal, Tangkak was sampled and incubated with 0 (control), 75 kg P/ha of TSP and KH2PO4 in the laboratory for ninety days at room temperature and at field capacity. Every ten days, the soil solution was collected using rhizon moisture sampler for determination of water-soluble As. A significant (P≤0.0001) increment in concentration of As was recorded with triple superphosphate (TSP) (76%) and potassium dihydrogen phosphate (KH2PO4) (69%) treatment compared to control. Three species of As present in the pore water with the amount of As(V) was higher than As(III) and undetectable value of MMA. In the glasshouse study, P. vittata was grown in soil added with 0 (control), 12.5, 25, 50 and 75 kg P/ha using TSP and KH2PO4 as P source. This study showed that addition of P in soil resulted in a significant increased in biomass of fronds. In contrast, a significant reduction in total concentration of As, up to 23 and 16% compared to the control. The present study, showed the addition of TSP had increased frond biomass of P .vittata better (38.94%) than KH2PO4 and the same time increased the As uptake (6.60 mg pot-1) in As rich soil. In conclusion, P. vittata was a suitable fern to be used for As accumulation in moderate concentration of As-rich soil with the addition of phosphate in soil because it can increase the availability of As for plant uptake due to the similarity in physico-chemical behavior.